Relationship between dietary inflammation index and frailty in patients with osteoarthritis - Feng Zhao; Fang Pan; Jian Li (Taylor & Francis Group, 2024)
Background Osteoarthritis (OA) is a common chronic joint disease that significantly affects an individual's quality-of-life and frailty has become one of the common complications in OA patients as the disease progresses. The relationship between dietary patterns is not clear.Methods All participants are from the National Health and Nutrition Examination Survey (NHANES) and have been diagnosed with OA. The dietary inflammation index (DII) is calculated based on the dietary intake reported by the participants. Logistic regression analysis is used to investigate the relationship between DII and frailty. Restricted cubic splines are utilised to explore their nonlinear relationship. Mediation analysis is conducted to explore the role of inflammation in this relationship.Results A total of 2,530 OA patients were included in the study, with an average age of 64.46 (12.67) years. After adjusting for covariates, for each one standard deviation increase in DII, the risk of frailty increased by 15% (OR = 1.15, 95% CI = 1.03-1.28). Compared to patients with DII < -1, patients with DII > 1 had a significantly higher risk of frailty (OR = 1.50, 95% CI = 1.05-2.14).Conclusions The findings of this study indicate a positive association between DII and the risk of frailty in OA patients. These results underscore the potential impact of dietary interventions in improving the quality-of-life for OA patients.